Hemolisis pada Produk Packed Red Cells dari Pendonor Obesitas - Artini, Dyah; Danarsih, Dwi Eni; Purnamaningsih, Nur'Aini (Jurnal Biomedika dan Kesehatan, 2025)
Background Obesity may affect the quality of transfused blood while it's being stored in the blood bag, according to studies. Through various pathways, obesity can alter the metabolism of red blood cells, increasing their vulnerability to hemolysis. Obese donors are currently not prohibited from donating blood by the Blood Transfusion Unit's donor selection examination. Therefore, there is still a substantial chance that blood products from obese donors will degrade in quality. The rate of hemolysis of blood components increases in direct proportion to the rise in the donor's body mass index (BMI). By using hemolysis as the primary metric, this study aims to investigate how obesity impacts the storage quality of PRC blood products. Methods The primary objective of this experimental study is to investigate the effect of fat donors on the quality of PRC blood products at the PMI Blood Donor Unit in Sleman Regency. The study included eight donors, divided into two groups: obese and non-obese. 350 cc of blood from each donor was processed into a platelet-rich plasma (PRC) component. The PRC component was subsequently examined hemologically and found to be hemolyzed. The Student T-Test was then used to explore the exam outcomes for each group. Results Both groups' PRC samples' hemolysis values and plasma hemoglobin levels increased during storage. There was an increase in plasma hemoglobin of 0.41 g/dL and a hemolysis value of 0.59% in the blood sample from the obese donor. When compared to the increase in the non-obese group, which was 0.34 g/dL and 0.47%, the value of this increase was higher. The analysis's results showed that there was no statistically significant difference between the sample groups' increase in hemolysis (p value = 0.732). Conclusions The study's findings showed that there is no statistically significant relationship between obesity and hemolysis in PRC products.